Optimization and mechanistic insights of zinc ascorbate catalyst for ring-opening polymerization of caprolactone using RSM methodology and DFT calculations - Naik, Sonali S.; Vedpathak, Shantanu; Nair, Kiran Sukumaran (Polymers for Advanced Technologies, 2025)
Polycaprolactone (PCL) is an aliphatic polyester recognized for its exceptional versatility and biodegradability, which has garnered significant attention for a wide range of applications. This study presents an innovative methodology for the synthesis of PCL through the ring-opening polymerization (ROP) of epsilon-caprolactone (CL). The approach employs a biocompatible and environmentally benign organometallic zinc ascorbate complex as a catalyst. Derived from ascorbic acid, a well-established reducing agent, zinc ascorbate serves as a sustainable alternative to conventional tin-based catalysts, thereby mitigating environmental impact and enhancing safety measures. The catalyst operates effectively under solvent-free conditions and does not require initiators, achieving a high polymer conversion rate of approximately 79%. The optimization of the reaction parameters was conducted using response surface methodology (RSM) employing a central composite design (CCD). The structural and chemical characterization of the catalyst as well as the resulting polymers was performed using proton nuclear magnetic resonance (1H NMR), Fourier-transform infrared spectroscopy (FTIR), and x-ray diffraction (XRD) analyses. Additionally, density functional theory (DFT) calculations elucidated a four-step coordination-insertion mechanism for the polymerization of cyclic lactones, with findings supported by Gibbs free energy, electrostatic potential, and non-covalent interactions. This study underscores the potential of zinc ascorbate as a reliable, nontoxic, and cost-effective catalyst, fulfilling the increasing demand for sustainable and efficient polymerization processes in commercial and biomedical applications.
Keywords: density function theory; Polycaprolactone; Response surface methodology; ring-opening polymerization; zinc ascorbate